Comparison of tonguecontours in childrenand adults: A preliminary ultrasound study - M, Irfana; N, Sreedevi (Journal of All India Institute of Speech and Hearing, 2013)
Ultrasound is a safe and non-invasive articulatory technique which tracks the shape of the tongue contours during the production of lingual sounds. Though ultrasound based studies are abundant in European languages, there are dearth of such studies in Indian languages. Kochetov et al (2012) studied lingual stops using ultrasound in native Kannada speaking adults and the results showed distinct tongue shapes for retroflex, dentals, and velars. They also reported that the retroflex consonants were predominantly sub-apical but the tongue body retraction is not an obligatory property of retroflexion. In this perspective, the present study is planned to compare the tongue contours for lingual stops across native Kannada speaking children and adults using ultrasound imaging. A total number of 20 subjects with equal number of children (9-10 years) and adults (23-25 years) participated in the study. The test material were three meaningful Kannada words; /atta/, /aTTa/ and /akka/ incorporating the dental /t/, UHWURIOH[ҀDQGYHODUN)RUUHFRUGLQJWKHVDPSOHWKHWUDQVGXFHUSUREHRIWKH0LQGUD\XOWUDVRXQG 6600 was placed beneath the participant’s chin. The software Articulate Assistant Advanced (AAA) ultrasound module (Version 2.14) was used for analysis. Smooth Spline Analysis of Variance (SSANOVA) was used to obtain the difference in the tongue contours. The results showed that tongue contours of children and adults are of similar patterns for the three places of articulation studied, but the overall height of the tongue contour is more in adults especially for the anterior tongue body region. The angle of retroflection was not prominent in both groups which reveal that retroflex sound production is not always sub-apical. This study augments our understanding about the similarities and differences in tongue dynamics across children and adults and it paves the way to understand better tongue dynamics in communication disordered population.